MRS. WELLINGTON'S ANXIETY IN GITTY DANESHVARI'S SCHOOL OF FEAR: THE FINAL EXAM - Novia Lestari Suwoto; Anik Cahyaning Rahayu (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
This study is entitled Mrs. Wellington’s anxiety reflected in Gitty Daneshvari’s School of Fear: The Final Exam. This study aims at describing the symptoms, the causes, and the effects of anxiety which is suffered by Mrs. Wellington. This study applies psychoanalysis theory by Sigmund Freud to analyze Mrs. Wellington’s anxiety. The symptoms of anxiety that is suffered by Mrs. Wellington are such as feeling anxious, being unable to think about anything but something that makes her anxious, and experiencing trembling, melancholy, and the deepest sadness. There are some causes of Mrs. Wellington’s anxiety. First, Mrs. Wellington’s anxiety is caused by her stepson, Abernathy, who hates her since he suffers from novercaphobia or well-known as fear of stepmother. The second cause is Sylvie Montgomery, the nosy reporter who always uses her nose to get information or disgraceful secret of Mrs. Wellington and all her students to make an article in order to win the Snoopulitzer, a contest for reporter in Summerstone. The effects of Mrs. Wellington’s anxiety are very complete. She feels the behavioral effect, the emotional effect, and the cognitive effect of her anxiety. It can be seen from her negative feeling because something in her past, she experiences trouble of concentrating, and she feels afraid every time she thinks about her fears. Mrs. Wellington’s anxiety is categorized of neurotic anxiety. Neurotic anxiety comes from id which is in the form of unconscious feeling so she often loses her emotion such as being sad, angry, panic, and so on. From the analysis, it can be concluded that Mrs. Wellington suffers from anxiety because her uncontrollable emotion: being anxious and being worried. Her stepson and Sylvie, the reporter, become the causes of her anxiety. She also feels the behavioral, emotional, and cognitive effects. Mrs. Wellington suffers from a type of neurotic anxiety as reflected in its symptoms, causes, and effects.